Psychological Safety in High-Performance Sport: Contextually Applicable? - Jamie Taylor; Jamie Taylor; Jamie Taylor; Dave Collins; Dave Collins; Michael Ashford; Michael Ashford (Frontiers in Sports and Active Living, 2022)
In recent years, high-performance sport has seen a rising interest in Psychological Safety, a construct with a strong empirical basis in certain business contexts. As research and practice interest grows in PS, there are early indications of practitioners and, to a lesser extent research, treating the construct as being universally transferable. We offer three central concerns with this situation. Firstly, it seems that a variety of different interpretations in use may limit the practical application of the construct. Secondly, a concern that not all dimensions of PS are transferable or applicable in the HPSs context, especially for athletes. Finally, emerging evidence from outside of sport suggests potential downsides to the perceptions of PS in a performance/selection sets. We suggest that, as with all theories and constructs, there is a pressing need for nuance and context-specific evidence in how researchers and practitioners approach transferability plus, perhaps, a little more understanding of the real-world high-performance context.